Salsa and the (Eternal) City. Rethinking the pleasure periphery - Ana, Ruxandra (Taylor & Francis Group, 2023)
This article takes as a starting point one of the classic metaphors in tourism studies, the ‘pleasure periphery’, in order to examine how the embodied labour of subaltern bodies establishes a regime of recognition, visibility, and value. Situated at the intersections of transnational migration, social mobility, and bodily work, this analysis follows the professional and personal trajectories of Cuban dancers in Europe. I discuss the various forms of exclusion that emerge at the intersection of dance consumerism, assumptions about migrant belongings, and hierarchies of performance practices. The ‘pleasure periphery’ serves as a spatial and symbolic metaphor that gives insight into the pivotal role of Cuban dance and music for the transnational dance scene, while shedding light on how peripheralization is reshaped and reproduced in migratory contexts. The transnational contexts of dance labour bring into focus the tensions between its emancipatory potential for Cuban performers and the perpetuation of consumption patterns and business strategies that reify peripherality on various levels (spatial, symbolic, and affective). The article is based on ethnographic fieldwork conducted in Havana, Cuba, and Rome, Italy among Cuban professional dancers and dance educators.
The Version of Record of this manuscript has been published and is freely available in Journal of Ethnic and Migration Studies, published online 10 August 2023, https://doi.org/10.1080/1369183X.2023.2245154.
Keywords: Cuba; migration; dance work; pleasure periphery; Italy